Gastrointestinal parasites of the chimpanzee population introduced onto Rubondo Island National Park, Tanzania - Petrzelková, Klára J; Hasegawa, Hideo; Appleton, Chris C; Huffman, Michael A; Archer, Colleen E; Moscovice, Liza R; Mapua, Mwanahamissi Issa; Singh, Jatinder; Kaur, Taranjit (American journal of primatology, 2010)
The release of any species into a novel environment can evoke transmission of parasites that do not normally parasitize the host as well as potentially introducing new parasites into the environment. Species introductions potentially incur such risks, yet little is currently known about the parasite fauna of introduced primate species over the long term. We describe the results of long-term monitoring of the intestinal parasite fauna of an unprovisioned, reproducing population of chimpanzees introduced 40 years earlier (1966-1969) onto Rubondo Island in Lake Victoria, Tanzania, a non-native habitat for chimpanzees. Two parasitological surveys (March 1997-October 1998 and October 2002-December 2005) identified Entamoeba spp. including E. coli, Iodamoeba buetschlii, Troglodytella abrassarti, Chilomastix mesnili, Trichuris sp., Anatrichosoma sp., Strongyloides spp., Strongylida fam. gen. sp., Enterobius anthropopitheci, Subulura sp., Ascarididae gen. sp., and Protospirura muricola. The parasite fauna of the Rubondo chimpanzees is similar to wild chimpanzees living in their natural habitats, but Rubondo chimpanzees have a lower prevalence of strongylids (9%, 3.8%) and a higher prevalence of E. anthropopitheci (8.6%, 17.9%) than reported elsewhere. Species prevalence was similar between our two surveys, with the exception of Strongyloides spp. being higher in the first survey. None of these species are considered to pose a serious health risk to chimpanzees, but continued monitoring of the population and surveys of the parasitic fauna of the two coinhabitant primate species and other animals, natural reservoir hosts of some of the same parasites, is important to better understand the dynamics of host-parasite ecology and potential long-term implications for chimpanzees introduced into a new habitat.
Keywords: Feces; gastrointestinální trakt; parazitární nemoci u zvířat; Entamoeba; Trichuris; Gastrointestinal Tract; mužské pohlaví; nemoci lidoopů; Nematoda; Retortamonadidae; Ape Diseases; Amoeba; ženské pohlaví; zvířata; feces; Tanzanie; Enterobius; Host-Parasite Interactions; Parasitic Diseases, Animal; interakce hostitele a parazita; Pan troglodytes; hlístice; Strongyloides; Tanzania; Ciliophora; Female; Male; Animals